2016
DOI: 10.4236/ojog.2016.64027
|View full text |Cite
|
Sign up to set email alerts
|

The Endometrium Biopsy and Hystero-Laparoscopy in Evaluation of Women’s Infertility. A Prospective Study in Algeria

Abstract: Female infertility is considered as a real obstacle to the development of a couple who cannot conceive in a natural way. The aim of this study is to evaluate female infertility using two complementary methods of exploration: hystero-laparoscopy and endometrial biopsy, to compare histopathological data with those of hystero-laparoscopy findings in the same patients, and finally assess the interest to couple both methods to detect a greater number of pathologies. Our prospective study included 64 patients aged 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…58 cases out of 75 cases (77.3%) studied. Similar findings have been documented by Kauret al 7 (77.14%) and Chelab et al 8 (71.90 %).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…58 cases out of 75 cases (77.3%) studied. Similar findings have been documented by Kauret al 7 (77.14%) and Chelab et al 8 (71.90 %).…”
Section: Discussionsupporting
confidence: 90%
“…In spite of biopsies sampled in the premenstrual phase, proliferative /anovulatory pattern was the most common cause of infertility. Similar findings were also observed by Girishet al 4 from Shimoga and Ikeme et al 11 in Nigeria and Cheleb et al 8 in Algeria. Other studies have found a secretory pattern to be more common which is an expected finding in a premenstrual biopsy.…”
Section: Discussionsupporting
confidence: 86%
“…Similar findings were also observed by Girish et al , 14 in India and Ikene et al in Nigeria 10 and Cheleb et al in Algeria. 9 However, other studies conducted in India and Pakistan, found secretory phase was the most common cause of infertility followed by proliferative phase. 8,11,15 Among the secretory phase we found late secretory phase was most frequent (25% cases).…”
Section: Discussionmentioning
confidence: 96%
“…Similar findings were also observed in the studies conducted by Kaur et al 8 in India and Chelab et al in Algeria. 9 Where they found women presented with primary infertility in 77.14% and 71.90 % cases respectively. Whereas, in Nigeria secondary infertility (61.7%) occurred more than primary infertility (38.3%).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation